2019
DOI: 10.1021/acsami.8b12621
|View full text |Cite
|
Sign up to set email alerts
|

Resonant and Selective Excitation of Photocatalytically Active Defect Sites in TiO2

Abstract: It has been known for several decades that defects are largely responsible for the catalytically active sites on metal and semiconductor surfaces. However, it is difficult to directly probe these active sites because the defects associated with them are often relatively rare with respect to the stoichiometric crystalline surface. In the work presented here, we demonstrate a method to selectively probe defect-mediated photocatalysis, through differential AC photocurrent (PC) measurements. In this approach, elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…In contrast, several studies on titanium dioxide (TiO x ) overlayers have indicated that the overlayer itself can facilitate electron transfer to/from its outer surface where active sites catalyze reactions of interest. [14][15][16] Various explanations for improved activity or selectivity of OECs have been proposed, including the ability of overlayers to facilitate selective species transport and/ or electronic interactions between the overlayer and electrocatalyst that enhance activity. 14,17,18 A deeper understanding of how ionic and electronic conductivities can affect the activity and selectivity of oxide overlayers is needed to inform rational design of OECs.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, several studies on titanium dioxide (TiO x ) overlayers have indicated that the overlayer itself can facilitate electron transfer to/from its outer surface where active sites catalyze reactions of interest. [14][15][16] Various explanations for improved activity or selectivity of OECs have been proposed, including the ability of overlayers to facilitate selective species transport and/ or electronic interactions between the overlayer and electrocatalyst that enhance activity. 14,17,18 A deeper understanding of how ionic and electronic conductivities can affect the activity and selectivity of oxide overlayers is needed to inform rational design of OECs.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of encapsulated electrocatalysts based on chromium oxide (CrOx) 9 , manganese oxide (MnOx) 12 , and silicon oxide (SiOx) 6,10 have provided evidence that the overlayers can act as ionically-conducting, electronically-insulating coatings that permit reactant/product species transport between the bulk electrolyte and active sites at the buried interface between the overlayer and catalyst. In contrast, several studies on titanium dioxide (TiOx) overlayers have indicated that the overlayer itself can facilitate electron transfer to/from its outer surface where active sites catalyze reactions of interest [13][14][15] . Various explanations for improved activity or selectivity of OECs have been proposed, including the ability of overlayers to facilitate selective species transport and/or electronic interactions between the overlayer and electrocatalyst that enhance activity 13,16,17 .…”
Section: Introductionmentioning
confidence: 99%